The teaching and learning of Mathematics via online : sharing a lifelong learning experience at Open University Malaysia - Ng , Richard (2014)
Today many working adults opted to pursue their dreams of getting a degree through open and distance learning (ODL) mode of studies. This is because the ODL option allows them the flexibility to study without having to leave their jobs or families behind. However, the flexibility in such learning mode means that learners have to depend on online support or other assistance for their extended learning. Mathematics, a traditionally difficult course, forms part of the pre-requisite for learners to obtain a business degree at Open University Malaysia (OUM). The majority of learners at OUM are adult learners who have left school for at least five years and most of them have low grades in Mathematics prior to embarking on their journey. Thus it is a big challenge for these adult learners to undertake a compulsory Mathematics course via online with minimum Face-to-Face contact with their tutors. A system of coaching ODL learners to understand and learn mathematics was developed known as the Online Supplemental Instruction (OSI) model at OUM. It involves the use of math video clips developed and posted on YouTube and organized in a web blog to assist learners. Mentoring was carried out via OUM’s online discussion forum available in OUM’s learner management system known as myVLE. This paper shares the award winning Lifelong Learning experience of developing the OSI model of teaching math via online and feedback obtained from learners who have used it successfully. (Abstract by author)